Thermodynamic analysis of a novel biomass-driven trigeneration system using different biomass resources - Parsa, Somayeh; Jafarmadar, Samad; Neshat, Elaheh; Javani, Nader (SPRINGER HEIDELBERG, 2024)
The present study proposes a novel system for power, heat, and hydrogen generation comprising a biomass gasification unit, Rankine cycle, dual-fuel combustion engine, and a waste heat recovery unit. Exhausting hot gases from the engine is recovered for the gasification of the biomass. A part of the generated hydrogen serves as the second fuel in a Heptane-fueled engine to improve its performance. Energy and exergy analyses are carried out for Sugarcane bagasse, Rice Straw, Wheat Straw, and Rice Husk biomass fuels. A good consistency can be seen between the findings of the current study and experimental reports in the literature. The developed trigeneration system improved both exergy efficiency and thermal efficiency by 19% when compared to the conventional system. The exergy efficiency is maximized by using sugarcane bagasse. Furthermore, the results show that Wheat Straw has a maximum total thermal efficiency of 95%. The maximum system exergy destruction of 54% is observed by using Rice Straw and Rice Husk.
Keywords: Biomass gasification; Waste heat recovery; Exergy efficiency; Trigeneration system; COMPRESSION IGNITION ENGINE; OXIDE FUEL-CELL; FLUIDIZED-BED; GAS-TURBINE; STEAM-GASIFICATION; REFORMER GAS; HEAT; EXERGY; POWER; COGENERATION; Energy & Fuels; Engineering